2013
DOI: 10.1002/gcc.22102
|View full text |Cite
|
Sign up to set email alerts
|

Novel MIR143‐NOTCH fusions in benign and malignant glomus tumors

Abstract: Glomus tumors (GT) have been classified among tumors of perivascular smooth muscle differentiation, together with myopericytoma, myofibroma/tosis, and angioleiomyoma, based on their morphologic overlap. However, no molecular studies have been carried out to date to investigate their genetic phenotype and to confirm their shared pathogenesis. RNA sequencing was performed in three index cases (GT1, malignant GT; GT2, benign GT and M1, multifocal myopericytoma), followed by FusionSeq data analysis, a modular comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
118
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(127 citation statements)
references
References 33 publications
(30 reference statements)
3
118
0
Order By: Relevance
“…Previous reports have shown that MIR143HG exon 1 fuses with exon 29 of NOTCH3 leading to an increased expression of the 3′part of NOTCH3. 33 These results are in line with our data, although we could not identify the 5′partner. It could be noted that neither NOTCH3 nor MIR143HG maps to chromosome bands involved in the translocation t(3;7) in this case.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Previous reports have shown that MIR143HG exon 1 fuses with exon 29 of NOTCH3 leading to an increased expression of the 3′part of NOTCH3. 33 These results are in line with our data, although we could not identify the 5′partner. It could be noted that neither NOTCH3 nor MIR143HG maps to chromosome bands involved in the translocation t(3;7) in this case.…”
Section: Discussionsupporting
confidence: 88%
“…Glomus tumors belong to the pericytic subgroup of soft tissue tumors, and fusions involving the micro RNA MIR143HG as the 5′ gene with any of NOTCH1, NOTCH2, or NOTCH3 as the 3′partner gene have previously been reported in these tumors. 33 We thus investigated the fusion further. Visualizing the reads generated from RNA-Seq in the Integrative Genomics Viewer (IGV; https://www.broadinstitute.org/igv/home) showed that there were more reads in the 3′part of the NOTCH3 gene, exons 25-33, indicating that this part was expressed at higher levels than the rest of the gene (Supplementary Figure 1) and in agreement with a rearrangement resulting in a split of the gene.…”
Section: Discussionmentioning
confidence: 99%
“…3 However, MIR143-NOTCH gene fusion often seen in glomus tumor has not been found in glomangiopericytoma. 27 In this study, further differences between glomangiopericytoma and glomus tumor included nuclear b-catenin expression and gain-of-function CTNNB1 mutations in glomangiopericytoma. Previous studies on glomus tumor, by contrast, showed a lack of b-catenin nuclear expression and CTNNB1 activating mutations.…”
Section: Discussionmentioning
confidence: 94%
“…9 Another recent study failed to demonstrate any rearrangements of NOTCH1-3 genes in five cases of SN-HPCs analyzed. 24 Accordingly, absence of similar alterations in SN-HPCs suggested a different, albeit yet unknown, molecular pathway involved in these morphologically distinctive tumors confined to the sinonasal tract.…”
Section: B-catenin Mutations In Sn-hpcmentioning
confidence: 99%